Ethnic differences in resting metabolic rate, respiratory quotient and body temperature: a comparison of Africans and European Australians - Adzika Nsatimba, P.; Pathak, K.; Soares, Mario (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2015)
Purpose: A comparison of resting metabolic rate (RMR), respiratory quotient (RQ) and body temperature between adults of African and European descent. Method: Twenty-nine sub-Saharan Africans (SSA; 13 men and 16 women) and thirty-two Australians of European descent (EUR; eight men and 24 women) had RMR and RQ measured by indirect calorimetry. Dual-energy X-ray absorptiometry was used to determine fat mass (FM), fat-free mass, bone mineral content (BMC), appendicular lean tissue mass and non-appendicular lean tissue mass. Total skeletal muscle mass (SMM) was predicted. Residual mass (RM) was the difference between body weight and the sum of FM, SMM and BMC. The short form of the International Physical Activity Questionnaire was used to determine habitual physical activity (PA). Tympanic in the ear temperature (IET) and forearm to fingertip temperature gradients (FFG) were monitored throughout the protocol. Results: The unadjusted RMR of SSA was significantly lower compared to EUR. Adjusted for age, sex, season, PA, FM, BMC, SMM and RM, this difference in RMR was still evident (mean ± SE, SSA: 4880 ± 161 kJ/d vs. EUR: 5979 ± 111, P < 0.005). The same model of adjustment also uncovered a significantly lower adjusted IET (SSA: 35.26 °C ± 0.133 vs. EUR: 35.60 ± 0.091, P < 0.05), a higher adjusted RQ (SSA: 0.86 ± 0.014 vs. EUR: 0.83 ± 0.010, P < 0.05) but no difference in adjusted FFG. Conclusions: In this study, SSA had a lower RMR, higher RQ and lower IET relative to EUR Australians.